Pelaksanaan Sistem Informasi Manajemen Kepegawaian Berbasis IT di Kantor Kementrian Agama Kabupaten Aceh Timur - Rimayanda; Maknuni, Jauharil (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2022)
The objective of the study was to determine the personnel management system, in particular the Personnel Management Information System (SIMPEG) and the Regional Civil Service Agency (BKD) of Nanggroe Aceh Darussalam. The Government Personnel System is for the smooth running of organizational tasks and becomes a supporting element for the implementation of the functions of the management of an organization, the existence and smoothness of administrative activities. Utilization of information technology can produce efficiency in various aspects of information management as indicated by the speed and timeliness of processing, as well as the accuracy and correctness of the information (validity) produced. The benefit of recording Personnel data is as a means to store personnel data systematically, making it easier to retrieve if needed. Personnel data is processed into staffing information, which is very necessary for employee development materials. Personnel management, both managerial and technical-administrative in nature, is always related to data, in the form of printed or electronic data.